Overexpression of CsSAMT in Citrus sinensis Induces Defense Response and Increases Resistance to Xanthomonas citri subsp. citri - Nascimento, Cesar Augusto; Teixeira-Silva, Natalia Sousa; Caserta, Raquel; Marques, Marcia Ortiz Mayo; Takita, Marco Aurelio; de Souza, Alessandra A. (Frontiers in Plant Science, 2022)
Citrus canker is a destructive disease caused by Xanthomonas citri subsp. citri, which affects all commercial sweet orange (Citrus sinensis [L.] Osbeck) cultivars. Salicylic acid (SA) and systemic acquired resistance (SAR) have been demonstrated to have a crucial role in mediating plant defense responses against this phytopathogen. To induce SAR, SA is converted to methyl salicylate (MeSA) by an SA-dependent methyltransferase (SAMT) and translocated systemically to prime noninfected distal tissues. Here, we generated sweet orange transgenic plants (based on cvs. Hamlin and Valencia) overexpressing the SAMT gene from Citrus (CsSAMT) and evaluated their resistance to citrus canker. We obtained four independent transgenic lines and confirmed their significantly higher MeSA volatilization compared to wild-type controls. Plants overexpressing CsSAMT showed reduced symptoms of citrus canker and bacterial populations in all transgenic lines without compromising plant development. One representative transgenic line (V44SAMT) was used to evaluate SAR induction. Without inoculation, V44SAMT modulated CsSAMT, CsNPR1, CsNPR3, and CsWRKY22 expression, indicating that this plant is in a primed defense status. The results demonstrate that MeSA signaling prompts the plant to respond more efficiently to pathogen attacks and induces immune responses in transgenic plants at both primary and secondary infection sites